Long-term storage and viability of Ochlerotatus albifasciatus (Diptera: Culicidae) - Raúl E Campos (Memorias do Instituto Oswaldo Cruz, 2008)
The viability of Ochlerotatus albifasciatus (Macquart) eggs stored at room temperature and at 5ºC was studied over 31 months. After 12, 18 and 31 months of storage, eggs were acclimatized at 22ºC for ten days, and then inundated twice every seven days. The effect of the storage period on the percentage of hatching was analyzed by one way ANOVA. Differences on the hatching response between the first and second flooding were analyzed by paired t-test. Differences on the hatching response between the two storage conditions were analyzed by Mann-Whitney rank test. Results showed that (1) Oc. albifasciatus eggs were able to survive and hatch over 31 months; (2) the percent hatching of eggs stored at 5ºC was higher than that of eggs stored at room temperature; and (3) low temperatures and long periods without water favor installment hatching.